Epidemiologic, clinical and therapeutic features of primary cutaneous lymphomas in Morocco - Fouzia Hali; Salma Zakaryaa; Karima Senouci; Zineb Zeggwagh; Fatima Zahra Mernissi; Sara Elloudi; Fatima Zahra Hashas; Said Amal; Ouafa Hocar; Maryem Aboudourib; Awatef Kelati; Inas Chikhaoui; et al. (Wiley, 2024)
Abstract Background Few epidemiological studies on primary cutaneous lymphomas are available and related to limited populations. Objectives To characterize the epidemiologic, clinical and therapeutic features of primary cutaneous lymphomas from a global perspective at the national level. Methods A cross‐sectional descriptive multicenter study including patients treated for cutaneous lymphomas at dermatology and venereology departments of different university hospitals in the kingdom of Morocco from January 2012 to December 2021. Results Our multicenter cohort consisted of 402 patients. The median age was 56 years (15-114) with a male predominance (61%, 245 cases). Based on the WHO‐EORTC classification, the most frequent histological type was cutaneous T‐cell lymphoma (CTCL) (88% of cases). Of these, mycosis fungoides (MF) was the most common (78%). B‐cell lymphomas represented 12% of cases, mainly centro‐follicular B‐cell lymphoma (40%). The clinical presentation was most frequently erythematous and scaly infiltrated lesions in 187 CTCL patients (52.6%), and nodular lesions in 37 patients (78%) with B‐cell lymphomas. Treatment modalities depended on the tumour's histological type and stage and included: topical corticosteroids and phototherapy in 52% of cases, monochemotherapy, radiotherapy, photopheresis and polychemotherapy. The evolution was marked by remission in 41% of patients, relapse in 17% and death in 12%. Conclusions Our national study provides data on primary cutaneous lymphomas in Morocco, never before mentioned in indexed literature. We identified 402 cases over a 10‐year period. A better knowledge of these entities is key to optimize diagnosis and therapy.